Comparing Sniffing Position Between Inflatable Vs Fixed Pillow for Glottic Visualization during Laryngoscopy - Adiyanto, Bowo; Ikhwandi, Arif (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2025)
Background: Effective glottic visualization is crucial for successful tracheal intubation and reducing complications during airway management. The sniffing position is commonly used, with various pillow types employed to optimize the alignment of the airway axes. We performed a study to evaluate the effectiveness of an inflatable intubation pillow for glottic visualization, intubation time, and first-attempt intubation success.Objective: We performed a study to evaluate the effectiveness of an inflatable intubation pillow for glottic visualization, intubation time, and first-attempt intubation success.Methods: A randomized controlled trial was conducted with 222 patients undergoing general anesthesia and endotracheal intubation at Dr. Sardjito General Hospital, Yogyakarta. Patients were randomly assigned to two groups: Group I (inflatable pillow) and Group S (fixed pillow). The primary outcome was glottic visualization, assessed using the Cormack–Lehane score, while secondary outcomes included intubation time and the number of intubation attempts. Multivariate analyses adjusted for potential confounders such as BMI, sex, and age.Results: The inflatable pillow group showed a higher proportion of grade 1 glottic visualization (64%) compared to the fixed pillow group (55%), but this difference was not statistically significant after adjusting for confounders. The inflatable pillow group demonstrated a significantly shorter intubation time (35 seconds) compared to the fixed pillowConclusion: The use of an inflatable pillow in the sniffing position significantly reduced intubation time, improving procedural efficiency. However, it did not show a significant improvement in glottic visualization or first-attempt intubation success after adjusting for confounding factors. BMI was the primary determinant of glottic visualization